Splitting failure and deformation evolution of the red argillaceous siltstone disc in the high humidity environment - Zhao, Zenghui; Dong, Zhongtai; Gao, Xiaojie; Liu, Hao (Frontiers in Materials, 2023)
The failure mechanism of weakly cemented soft rock under water-rock coupling effect is extremely complex. To reveal the tensile failure of red argillaceous siltstone in high humidity environment, five kinds of disc samples with different water contents were obtained through maintenance in constant temperature and humidity oven. The Brazilian test was carried out to reveal the variation characteristics of splitting behavior of rock samples in high humidity environment. Detailed analysis was conducted on the evolution law of stress-strain relationship and mechanical parameters under five different water contents. Combined with the DIC (Digital Image Correlation) investigation, the displacement evolution patterns of samples with different water content and loading stages were analyzed. Results show that he macroscopic mechanical parameters such as tensile strength and elastic modulus of weakly cemented red sandstone samples under water environment are negatively parabolic correlated with the increase of water content. The moisture content has an important influence on the disc splitting failure mode, forming the main fracture along the radial direction of loading, and showing a local crushing area in the loading area, and the crushing area increases with the increase of water content. Microstructural variation of red sandstone under a high humidity environment is the main reason for its deterioration of macroscopic mechanical properties.